Bounding the rotating wave approximation for coupled harmonic oscillators - Heib, Tim; Lageyre, Paul; Ferreri, Alessandro; Wilhelm, Frank K.; Paraoanu, G. S.; Burgarth, Daniel; Schell, Andreas W.; Edward Bruschi, David (Journal of Physics A: Mathematical and Theoretical, 2025)
In this work we study the validity of the rotating wave approximation of an ideal system composed of two harmonic oscillators evolving with a quadratic Hamiltonian and arbitrarily strong interaction. We prove its validity for arbitrary states by bounding the error introduced. We then restrict ourselves to the dynamics of Gaussian states and are able to fully quantify the deviation of arbitrary pure Gaussian states that evolve through different dynamics from a common quantum state. We show that this distance is fully determined by the first and second moments of the statistical distribution of the number of excitations created from the vacuum during an appropriate effective time-evolution. We use these results to completely control the dynamics for this class of states, therefore providing a toolbox to be used in quantum optics and quantum information. Applications and potential physical implementations are also discussed.
CRIS-Team Scopus Importer:2025-05-09
Keywords: quantum dynamics; quantum harmonic oscillators; quantum optics; rotating wave approximation